Bibliometric Computational Mapping Analysis of Publications on Financial Technology in Islamic Capital Market - Ahmad Fadlur Rahman Bayuny; Yana Rohmana (Universitas Pendidikan Indonesia, 2022)
Purpose – This study aims to explore and categorize research literature on Financial Technology in Islamic Capital Market systematically by mapping and visualizing it through bibliometric analysis using VOSviewer. Methodology - The research from publications that have appeared in journals that are indexed by Google Scholar served as the foundation for the article data used in this study. A reference manager tool called Publish or Perish is used to gather research data. A literature review on the subject we chose was done with the help of the program Publish or Perish. Findings - The results show that research on Financial Technology in Islamic Capital Market is separated into 3 terms: Financial Technology, Islamic, Capital Market. The term